Computerised lung auscultation: sound software (CLASS) - Semedo, José (2018)
Computer-assisted learning tools have been shown to promote self-directed learning and enhance problem-solving skills. However, few have been developed in the area of respiratory medicine and the majority does not include all the required features for integration of knowledge (e.g., sound recording and analysis). Thus, we aimed to develop and evaluate an open-source computer-assisted learning application for respiratory sound recording, analysis and interpretation, the Computerised Lungs Auscultation – Sound Software (CLASS). CLASS is the only computer-assisted learning tool which simultaneously allows the recording and analyses of respiratory sounds. The usability of CLASS has been tested by eight physiotherapy students through an open-ended questionnaire and a focus group interview. Participants highlighted its utility and great potential to be used in academic and clinical environments, and they also identified some drawbacks. New developments are being incorporated to improve CLASS usability in the academic context but also to make it available in health professionals’ clinical practice.